Amoxicylin-Klavulanate and Cefadroxyl Resistance Toward Staphylococcus Aureus Isolate from Children's Nose Mucosa - Valzon, May; Siagian, Dewi Sartika; Agusmai, Riski (Universitas Aisyah Pringsewu, 2021)
Developing countries play an important role in the emergence of bacterial resistance to antibiotics because they are home to the majority of the world's population. Increased bacterial resistance to antibiotics has been widely reported, one of which is Staphylococcus Aureus against various ?-lactam antibiotics. The high level of resistance to amoxicillin causes the use of amoxicillin-clavulanate to start increasing in the community even without culture data or epidemiological data. Antibiotics that are often used in the treatment of fever complaints in children in Indonesia are cefadroxil, followed by cefixime and amoxicillin. This research objective was to analyze the antibiotic resistance of amoxicillin-clavulanate and cefadroxil against Staphylococcus Aureus bacteria in children. This research used Staphylococcus Aureus samples from the nasal mucosa of healthy children. Cultures were tested with an antibiotic disk of amoxicillin-clavulanate, cefadroxil and cefoxitin using the Kirby-Bauer diffusion disk method to assess the zone of inhibition of each antibiotic. The diameter of the growth inhibition zone of Staphylococcus aureus was different between amoxicillin-clavulanate and cefadroxil. Amoxicillin-clavulanate has experienced resistance in 5 of the 6 samples tested while cefadroxil is sensitive to the 6 tested samples so it can be concluded that amoxicillin-clavulanate has been resistant and cefadroxil is still sensitive to Staphylococcus Aureus. Abstrak: Negara berkembang memegang peranan penting dalam kemunculan resistensi bakteri terhadap antibiotik karena merupakan tempat tinggal bagi mayoritas penduduk dunia. Peningkatan resistensi bakteri terhadap antibiotik telah banyak dilaporkan, salah satunya Staphylococcus aureus terhadap berbagai antibiotik golongan ?-laktam. Tingginya tingkat resistensi terhadap amoksisilin menyebabkan penggunaan amoksisilin-klavulanat mulai meningkat di masyarakat walaupun tanpa data kultur atau data epidemiologi. Antibiotik yang sering digunakan dalam terapi keluhan demam pada anak di Indonesia adalah sefadroksil , diikuti oleh sefiksim dan amoxicillin. Penelitian ini bertujuan untuk menganalisis resistensi antibiotik amoksisilin-klavulanat dan sefadroksil terhadap bakteri Staphylococcus aureus pada anak. Penelitian ini menggunakan sampel Staphylococcus aureus hasil kultur dari mukosa hidung anak sehat. Kultur di uji dengan disk antibiotik amoksisilin-klavulanat, sefadroksil dan cefoxitin dengan metode disk difusi Kirby-bauer untuk menilai zona hambat masing-masing antibiotik. Diameter zona hambat pertumbuhan Staphylococcus aureus berbeda antara amoksisilin-klavulanat dengan sefadroksil. Amoksisilin-klavulanat telah mengalami resistensi pada 5 dari 6 sampel yang diuji sedangakn sefadroksil sensitif terhadap 6 sampel yang diuji sehingga dapat disimpulakn bahwa amoksisilin-klavulanat telah resisten dan sefadroksil masih sensitif terhadap Staphylococcus aureus.